The Vermes quest: the significance of Geza Vermes for Jesus research - Møller, Hilde Brekke (Library of New Testament studies, 2017)
Acknowledgements -- Abbreviations -- Part I: Introduction -- Ch. 1: The Significance of Geza Vermes for Jesus Research -- Ch. 2: Vermes and Jesus Research -- Ch. 3: The History of Jesus Research: Mapping the Quest(s) -- Ch. 4: Vermes' Jewish Jesus (1973) -- Ch. 5: The Significance of Jesus the Jew (The 1970s and 1980s) -- Ch. 6: The Jewishness of Jesus Before Vermes -- Ch. 7: The Significance of Vermes' Work on the Son of Man -- Ch. 8: Final Considerations on the Jewishness of Jesus Within Jesus Research -- Part II: The Significance of Vermes' Hasid Theory -- Ch. 9: Vermes's Hasid Theory and its Precursors -- Ch. 10: The Hasid Theory Within Jesus Research After 1973 -- Ch. 11: Hanina Ben Dosa Heals From a Distance: A Case of Christian Influences Upon Talmudic Judaism? -- Part III: Conclusions and Outlook -- Ch. 12: Conclusion -- Ch. 13: Outlook -- Bibliography -- Index